Production Structure, Output and Profits- A Note - Dögüs, Ilhan (Brazilian Keynesian Review, 2024)
This paper argues that the case of product differentiation of concentrated markets (i.e., innovation competition) is one where production per unit of profit of non-financial corporations is lower than in competitive mass production and profit share is not an increasing function of capacity utilisation. Rather the desired excess capacity is higher since the break-even point where total costs and revenues equalize tends to be lower. The argument is supported with descriptive annual data for the period 1947-2019 in the USA.